A porous 3D-RGO@MWCNT hybrid material as Li–S battery cathode - Zhang, Yongguang; Ren, Jun; Zhao, Yan; Tan, Taizhe; Yin, Fuxing; Wang, Yichao (Beilstein Journal of Nanotechnology, 2019)
In this work, a unique three-dimensional (3D) structured carbon-based composite was synthesized. In the composite, multiwalled carbon nanotubes (MWCNT) form a lattice matrix in which porous spherical reduced graphene oxide (RGO) completes the 3D structure. When used in Li–S batteries, the 3D porous lattice matrix not only accommodates a high content of sulfur, but also induces a confinement effect towards polysulfide, and thereby reduces the “shuttle effect”. The as-prepared S-3D-RGO@MWCNT composite delivers an initial specific capacity of 1102 mAh·g−1. After 200 charging/discharge cycles, a capacity of 805 mAh·g−1 and a coulombic efficiency of 98% were maintained, implying the shuttle effect was greatly suppressed by the composite matrix. In addition, the S-3D-RGO@MWCNT composite also exhibits an excellent rate capability.
Keywords: carbon nanotubes; energy storage and conversion; Li–S batteries; nanocomposites